The Influence and Contribution of Financial Performance to Firm Value: A Study on Manufacturing Companies Listed on the Indonesia Stock Exchange - I Ketut Mangku; Andika, Andika; Della Nanda Luthfiana; Agustina Gabyanti Kleden (DINASTI RESEARCH, 2024)
This research, titled “The Influence and Contribution of Financial Performance to Firm Value: A Study on Manufacturing Companies in the Indonesia Stock Exchange,” aims to assess the impact and contribution of financial performance on firm value. Financial performance is measured using Return on Assets, debt-to-assets ratio, Total Assets Turnover, and Dividend Payout Ratio, while firm value is proxied using price-to-book value. The sample is determined through purposive sampling, and multiple linear regression analysis is employed to examine the influence of financial performance variables on firm value. The research findings indicate that Return on Assets and Debt to Assets Ratio have a significant favorable influence. Meanwhile, Total Assets Turnover has a non-significant negative impact, and the Dividend Payout Ratio has a positive but non-significant effect on firm value. Approximately 6.9% of the variability in firm value can be explained by financial performance variables. Implications: The findings of this research provide insights for investors in making investment decisions and underscore the importance of understanding financial performance and its impact on firm value